Perangkat Pembelajaran Usaha dan Energi Berbasis STEM Terintegrasi Kearifan Lokal Timba Laor di Negeri Allang Kabupaten Maluku Tengah - Anatasija Limba; Clara Levenia Jamarua (Univiversitas Dr. Djar Wattiheluw, 2021)
21st-century learning should include STEM to grow interested in the Indonesian nation to love and master science, technology, engineering, and mathematics. They are included in it for physics learning. STEM is a practical learning approach because it combines knowledge, mathematics, technology, and techniques. This aim to make students as problem-solvers, inventors, have innovation, independent logical thinking, technological literacy, connect their culture and history with education, and apply their knowledge in real life. Thus, it is necessary to implement STEM-based learning integrated lokal wisdom /culture of the community in which the learners are located. One of the lokal wisdom of coastal communities in Maluku is Timba Laor. This research aims to develop a High School Physics Learning Tool business concept, and STEM-based Energy integrated lokal wisdom Timba Laor in the village of Allang Central Maluku district, a valid, practical, and effective Plomp model. The stages of mining carried out in this research activity are the development of high school physics learning tools business concept and STEM-based Energy integrated lokal wisdom Timba Laor in the village of Allang Central Maluku District. Test models by providing surveys of physics teachers to empirically validate the learning devices that have been compiled, analyzed, and revised. The resulting product is a learning device physics high school concept business, and energy-based STEM integrated lokal wisdom.